2006
DOI: 10.1016/j.jmb.2006.08.057
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determinants Involved in the Regulation of CXCL14/BRAK Expression by the 26 S Proteasome

Abstract: The chemokine CXCL14/BRAK participates in immune surveillance by recruiting dendritic cells. CXCL14 gene expression is altered in a number of cancers, but protein expression levels have not been investigated. Here we report that CXCL14 protein can be expressed in primary epithelial cells, however in several immortalized and cancer cell lines this protein is targeted for polyubiquitylation and proteasomal degradation. We determined the NMR structure of CXCL14 to identify motifs controlling its expression. CXCL1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 37 publications
2
30
0
1
Order By: Relevance
“…This can be explained with the high expression level of CXCL14 in stress conditions60. Such findings prompt speculation that CXCL14 expression is induced in response to stress61. In agreement with previous studies, CXCL14 has been shown to possess functions similar to other trophic factors62, such as the activation of endogenous survival mechanisms to enhance growth and to repair neural tissue63.…”
Section: Discussionsupporting
confidence: 81%
“…This can be explained with the high expression level of CXCL14 in stress conditions60. Such findings prompt speculation that CXCL14 expression is induced in response to stress61. In agreement with previous studies, CXCL14 has been shown to possess functions similar to other trophic factors62, such as the activation of endogenous survival mechanisms to enhance growth and to repair neural tissue63.…”
Section: Discussionsupporting
confidence: 81%
“…Cell lysates were prepared and Western blot analysis was carried out as previously described. 15 Tumor lysates were prepared by homogenizing excised tumor tissue in extraction buffer (0.1% CHAPS, 25 mM HEPES, 5 mM EDTA, 2 mM DTT). Extracts were flash frozen in liquid nitrogen and stored at -70°C.…”
Section: Methodsmentioning
confidence: 99%
“…This mechanism is very important in terms of angiogenesis, cell migration, and metastasis, all playing enormous roles in cancer (6669). The role of chemokines in metastasis is the outcome of modified presentation of G-protein coupled receptors.…”
Section: The 26s Proteasome Complex In Different Cellular Events and mentioning
confidence: 99%